Scavenging of nitric oxide up-regulates photosynthesis under drought in Festuca arundinacea and F. glaucescens but reduces their drought tolerance - Dawid Perlikowski; Katarzyna Lechowicz; Izabela Pawłowicz; Magdalena Arasimowicz-Jelonek; Arkadiusz Kosmala (Scientific Reports, 2022)
Abstract Nitric oxide (NO) has been proven to be involved in the regulation of many physiological processes in plants. Though the contribution of NO in plant response to drought has been demonstrated in numerous studies, this phenomenon remains still not fully recognized. The research presented here was performed to decipher the role of NO metabolism in drought tolerance and the ability to recover after stress cessation in two closely related species of forage grasses, important for agriculture in European temperate regions: Festuca arundinacea and F. glaucescens. In both species, two genotypes with distinct levels of drought tolerance were selected to compare their physiological reactions to simulated water deficit and further re-watering, combined with a simultaneous application of NO scavenger, 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (PTIO). The results clearly indicated a strong relationship between scavenging of NO in leaves and physiological response of both analyzed grass species to water deficit and re-watering. It was revealed that NO generated under drought was mainly located in mesophyll cells. In plants with reduced NO level a higher photosynthetic capacity and delay in stomatal closure under drought, were observed. Moreover, NO scavenging resulted also in the increased membrane permeability and higher accumulation of ROS in cells of analyzed plants both under drought and re-watering. This phenomena indicate that lower NO level might reduce drought tolerance and the ability of F. arundinacea and F. glaucescens to recover after stress cessation.